Effect of soil types, soil pasteurisation and inoculation on the growth of Colophospermum mopane families : a nursery study - Hangula, Rusta J. K.(Rusta Justa Kusta) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1998.